Independent path-based process recommendation algorithm for improving biomedical process modelling - Wang, Jiaxing; Tan, Dapeng; Cao, Bin; Fan, Jing; Deep, Samundra (Electronics letters, 2020)
Process recommendation is an important technique in business process management (BPM), which can be introduced to support modelling biomedical processes. However, most existing process recommendation algorithms in terms of behaviour (what tasks need to be executed in what order) suffer from the problem of state-space explosion when unfolding a process with many parallel patterns. To address this issue, the authors propose an independent path-based process recommendation algorithm to speed up the biomedical process recommendation while guaranteeing the accuracy. The experimental results of the proposed algorithm showed higher accuracy and better efficiency than the state-of-the-art algorithms.